Diagnóstico fitosanitario de theobroma cacao l. en diferentes tratamientos de biochar + humus-biol en la parroquia pagua (el oro-ecuador). - Rizzo Muñiz, Jefferson Manuel (Machala : Universidad Técnica de Machala, 2021)
The cultivation of cocoa is of great importance since it is the livelihood of many families in Ecuador, and due to its geographical location it has the ideal conditions for a good development of the plant and therefore a good production, the largest planted area is in the coastal region. The enormous use of chemicals causes it to generate pollution not only in the crop but also in the environment, as an alternative the use of organic amendments is implemented that help to recover the life of the soil such as the use of humus, biol, compost, biochar among others so that the plant can better absorb the nutrients, and a tolerance is achieved to certain pests and diseases present in the plantation.In recent years, the use of biochar in agricultural soils has taken off, it should be noted that to obtain results it will depend on what type of material is going to be used for its preparation, the time of the production process (pyrolysis). Having said this, the objective of the research work was to analyze the effect of the different amendments to the soil of Biochar + Humus + Biol in the phytosanitary control of Theobroma Cacao L., Clone CCN51 by means of phytosanitary agronomic parameters. sector “Sabanas de pagua” Cantón el Guabo province of El Oro where a plot of the farm was chosen, with a block design, where 5 study units were established and the treatments were assigned each with fifteen repetitions. The treatments to be carried out consist of applying different doses of biochar (banana cocoa peel) + Humus + Biol (100 g and 150 g), with a control that only humus + Biol was placed on it. The variables under study were healthy pods. diseased ears, total ears, ear weight, ear diameter, ear length, number of kernels per ear, weight of one hundred wet seeds and one hundred dry seeds. In the agronomic quantifications it was possible to establish that the T1 showed a difference in the diameter of the ear with an average of 30.71 cm. In the length of the ear, it was obtained that T0 has the highest value in the length of the ear with an average of 20.67 cm. The weight of the cob was evidenced that the T0 treatment was the one that gave us the highest value with an average of 707g.Treatment T0 was the one with the highest wet weight with an average of 463g, treatment T1 was the one with the highest dry weight giving an average of 186g. It was diagnosed that in the treatment T0 it was of higher presence of healthy ears with a mean of 13.54. It was evidenced that treatments T4 and T0 showed a greater number of ears with a total of 50 units. It was determined that the T4 treatment was the one that presented the lowest incidence of diseased ears, obtaining an average of 1.9619. It was determined that the T0 obtained the highest total of ears per treatment represented by 17 units. It can be recommended that the dose T4 of cocoa biochar 75g + humus75g + biol helped to reduce the proliferation of the disease.
El cultivo de cacao es de gran importancia ya que es sustento de muchas familias en el Ecuador, y por su ubicación geográfica cuenta con las condiciones idóneas para un buen desarrollo de la planta y por ende una buena producción, la mayor área sembrada se encuentra en la región costanera. El uso descomunal de químicos hace que genere una contaminación no solo en el cultivo si no ambiental, como alternativa se implanta el uso de enmiendas orgánicas que ayudan a recuperar la vida del suelo como por ejemplo el uso de humus, biol, compost, biochar entre otros para que la planta pueda absorber mejor los nutrientes, y se logre una tolerancia a ciertas plagas y enfermedades presentes en la plantación. Los últimos años ha tomado apogeo el uso de biochar en suelos agrícolas cabe destacar que para obtener resultados dependerá de que tipo de material se va a utilizar para su elaboración, el tiempo de proceso de obtención (pirolisis). Dicho esto, el trabajo investigación tuvo como objetivo Analizar el efecto de las diferentes enmiendas al suelo de Biochar+Humus+ Biol en el control fitosanitario del Theobroma Cacao L., Clon CCN51 mediante parámetros agronómicos fitosanitarios ., Se efectuó una investigación experimental de campo en el sector “Sabanas de pagua” Cantón el Guabo provincia de El Oro donde se escogió una parcela de la finca, con un diseño por bloques, donde se establecieron 5 unidades de estudio y se asignó los tratamientos cada uno con quince repeticiones. Los tratamientos a efectuarse consisten en aplicar diferentes dosis de biochar (cascara de cacao- raquis de banano) +Humus+Biol (100 g y 150 g), con un testigo que solo se le colocara Humus+ Biol. las variables en estudio fueron mazorcas sanas. mazorcas enfermas, total de mazorcas, peso de mazorca, diámetro de mazorca, longitud de mazorca, número de almendras por mazorca, peso de cien semillas húmedas y cien semillas secas. En las cuantificaciones agronómicas se logró establecer que el T1 se notó una diferencia en el diámetro de la mazorca con un promedio de 30,71 cm. En la Longitud de la mazorca se obtuvo que el T0, tiene el mayor valor en la longitud de la mazorca con una media de 20,67 cm. El peso de la mazorca se evidencio que el tratamiento T0, fue la que nos dio un mayor valor con un promedio de 707g. El tratamiento T0 fue la de mayor peso en húmedo con una media de 463g, el tratamiento T1 fue la de mayor peso en seco dando una media de 186g. Se diagnosticó que en el tratamiento T0 fue de mayor presencia de mazorcas sanas con una media de 13,54. Se evidencio que en los tratamientos T4 y T0 mostraron mayor número de mazorcas con un total 50 unidades. Se determinó que el tratamiento T4 fue la que presento menor incidencia de mazorcas enfermas obtuvo un promedio de 1.9619. Se determinó que el T0 obtuvo el mayor total de mazorcas por tratamiento representado por 17 unidades. Se puede recomendar que el T4 de dosis de biochar de cacao 75g+humus75g+biol ayudo a disminuir la proliferación de la enfermedad.
Keywords: BIOCHAR; FITOSANIDAD; ENMIENDAS; ORGÁNICAS